1997
DOI: 10.1073/pnas.94.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of population and affluence on CO2 emissions

Abstract: We developed a stochastic version of the Impact ‫؍‬ Population⅐Affluence⅐Technology (IPAT) model to estimate the effects of population, affluence, and technology on national CO 2 emissions. Our results suggest that, for population, there are diseconomies of scale for the largest nations that are not consistent with the assumption of direct proportionality (loglinear effects) common to most previous research. In contrast, the effects of affluence on CO 2 emissions appear to reach a maximum at about $10,000 in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
745
3
25

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,563 publications
(796 citation statements)
references
References 23 publications
23
745
3
25
Order By: Relevance
“…climate change | energy | integrated assessment | population | households S tatistical analyses of historical data suggest that population growth has been one driver of emissions growth over the past several decades (1)(2)(3) and that urbanization (2), aging (3), and changes in household size (2) can also affect energy use and emissions. Demographers expect major changes in these dimensions of populations over the coming decades (4).…”
mentioning
confidence: 99%
“…climate change | energy | integrated assessment | population | households S tatistical analyses of historical data suggest that population growth has been one driver of emissions growth over the past several decades (1)(2)(3) and that urbanization (2), aging (3), and changes in household size (2) can also affect energy use and emissions. Demographers expect major changes in these dimensions of populations over the coming decades (4).…”
mentioning
confidence: 99%
“…According to the World Population Data Sheet (2015), in 2010 China had a population of 1,330.141.295 (1 st most populous country in the world), while Russia had a population of 139,390,205 (9 th most populous country in the world). Some scholars (Rohde, 1990;Lashof and Ahuja, 1990;Jenkinson et al, 1991;Dietz, 1997;Fearnside, 1997;Shine et al, 2005) consider the elevation of CO 2 levels in the atmosphere to be largely responsible for the intensification of the greenhouse effect. In historical terms, this elevation is attributed to the burning of fossil fuels (coal, oil, and natural gas) for power generation and, secondarily, to agricultural processes and the destruction of natural vegetation, such as forests (Andreae, 1991;Bodansky, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…STIRPAT is for Stochastic Impacts by Regression on Population, Affluence, and Technology. Please refer to [28,29] for a detailed information. Results from the ARDLBT method showed that income has a negative association with the electricity.…”
Section: Previous Studies Investigating Electricity Demand In Azerbaijanmentioning
confidence: 99%